EFFECT OF ORTHODONTIC TREATMENT ON PHONETICS. A SCOPING REVIEW - Suhael Ahmed, Lamyaa. A. Alajlan, Alanoud Almahmood, Muath. A. Alsuwailem, Amer. M. Aldosari, Abdulelah. S. Alali, Renad Mohammed Alasmari, Saad Almutairi, Ali. H. Alrimthi, Abdulrhman Aldawsari, Sarah Ali Saud Al-Taleb, Aljouhra Ibrahaim Almujaiwel,; Aalia Trad Alharthi, Salma Mushabbab S. Alahmari, (Chelonian Research Foundation, 2024)
Various orthodontic appliances, including fixed appliances, orthodontic retainers, and palate expanders, can potentially cause speech difficulties and can affect speech clarity. However, the impact of orthodontic equipment on speech impairments has not been thoroughly examined using an evidence-based approach. Appliances have the potential to distort the i, a, and e vowels, as well as the s, z, l, t, d, and r. While the majority of speech problems often resolve within a few weeks, the distortion of the s sound may persist for over 3 months. The objective of this study is to elucidate the scientific evidence and the processes underlying the speech impairments induced by orthodontic appliances. The study included randomized-controlled clinical trials (RCT), controlled clinical trials, and cohort studies that specifically examined the impact of orthodontic appliances on speech. The researchers performed a methodical search using electronic databases such as PubMed, Web of Science, and Scopus. The orthodontic appliances were categorized, and the specific sounds affected by them, as well as the duration of speech disturbances, were identified. The ROBINS-I tool was utilized to assess the quality of non-randomized studies, whereas the bias of RCTs was evaluated according to the guidelines outlined in the Cochrane Handbook for Systematic Reviews of Interventions. Out of the 364 articles that were reviewed, 10 studies were selected for inclusion in the study. In conclusion, it is evident. that lingual fixed appliances, palatal expanders, and Hawley retainers significantly impact speech output. The i, s, t, and d phonemes are the primary ones that are impacted. Keywords- Speech, orthodontic treatment, phonetics